2020
DOI: 10.1126/scisignal.aaz3334
|View full text |Cite
|
Sign up to set email alerts
|

PhoQ is an unsaturated fatty acid receptor that fine-tunes Salmonella pathogenic traits

Abstract: The Salmonella enterica PhoP/PhoQ two-component signaling system coordinates the spatiotemporal expression of key virulence factors that confer pathogenic traits. Through biochemical and structural analyses, we found that the sensor histidine kinase PhoQ acted as a receptor for long-chain unsaturated fatty acids (LCUFAs), which induced a conformational change in the periplasmic domain of the PhoQ protein. This resulted in the repression of PhoQ autokinase activity, leading to inhibition of the expression of Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…However, the administration of a CLA supplement failed to attenuate S. Typhimurium gut infection or systemic dissemination in the streptomycin infection model (Carabajal et al, 2020). Subsequent studies demonstrated that the periplasmic sensor domain in PhoQ likely interacts with various LCUFAs to inhibit its autophosphorylation (Carabajal et al, 2020). (Figure 2B) Finally, in addition to its phosphorylation by PhoQ, recent work has demonstrated that PhoP DNA binding activity is further modulated by the acetylation of lysine residues within its DNA binding domain (Ren et al, 2016;Li et al, 2021).…”
Section: Lcufa Sensing By Phoq In S Typhimuriummentioning
confidence: 99%
See 2 more Smart Citations
“…However, the administration of a CLA supplement failed to attenuate S. Typhimurium gut infection or systemic dissemination in the streptomycin infection model (Carabajal et al, 2020). Subsequent studies demonstrated that the periplasmic sensor domain in PhoQ likely interacts with various LCUFAs to inhibit its autophosphorylation (Carabajal et al, 2020). (Figure 2B) Finally, in addition to its phosphorylation by PhoQ, recent work has demonstrated that PhoP DNA binding activity is further modulated by the acetylation of lysine residues within its DNA binding domain (Ren et al, 2016;Li et al, 2021).…”
Section: Lcufa Sensing By Phoq In S Typhimuriummentioning
confidence: 99%
“…Accordingly, the HK receptor PhoQ becomes autophosphorylated in response to various environmental signals including moderate acid stress, osmotic stress, low Mg 2+ availability, and CAMPs (Fields et al, 1986;Fields et al, 1989). More recently, a screen of potential plant-derived inhibitors of PhoQ identified LCUFAs, and not saturated LCFAs, as exogenous signals that inhibit autokinase activity in PhoQ and repress PhoP regulated genes (Gastoń et al, 2013;Carabajal et al, 2020). Interestingly, this included conjugated linoleic acids (CLAs), which are common products of bacterial biotransformation reactions that occur in the gut.…”
Section: Lcufa Sensing By Phoq In S Typhimuriummentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, oleic acid induced oxidative stress responses in C. albicans and displayed broad effects, which included the modification of the ergosterol composition on the fungal cell membrane although the exact effects in an animal model are not known. A related unsaturated fatty acid, linoleic acid, has recently been shown to enhance Salmonella enterica gastrointestinal colonization dissemination to the spleen in a murine model [74]. Both of these studies suggest that lipids could play a complex role in the host gastrointestinal tract, providing beneficial or detrimental effects to the host, possibly influenced by the overall microbiota composition and state of the host immune response.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a handful of inhibitors are known to selectively target the Salmonella PhoP/PhoQ regulatory system in vitro . They include two quinazoline-based compounds, which target PhoQ histidine kinase activity, and some unsaturated fatty acids. Interestingly, a modulatory effect of long-chain polyunsaturated fatty acids along Salmonella infection has been observed in mice …”
Section: Introductionmentioning
confidence: 99%